2018
DOI: 10.22375/dbr.v2i0.27
|View full text |Cite
|
Sign up to set email alerts
|

Education Service Quality, Value and Satisfaction on Student Customer Intentions and Behaviour

Abstract: Traditional avenues of accreditation, module review and teaching evaluations are not the only ways to assess education service quality and related issues. In order to evaluate the education service provided by a private university in Ireland, this investigation utilized an extension of Cronin, Brady and Hult’s (2000) model examining the effects of quality, value and customer satisfaction on customer intentions and behaviour. The model predicts that positive perceptions of quality, value and satisfaction in rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…Fourth, there will be a variety of variables that can be mediated between service quality and loyalty. The theoretical review in this study confirmed that there are various variables that may be related to business service quality, such as value (Prentice, McLaughlin, & Brady, 2018;Sung, Kim, & Youn, 2014), motivation , attachment (Lee, Jung, & Seong, 2018), and trust (Lee & Bea, 2006).…”
Section: Limitationsupporting
confidence: 56%
See 2 more Smart Citations
“…Fourth, there will be a variety of variables that can be mediated between service quality and loyalty. The theoretical review in this study confirmed that there are various variables that may be related to business service quality, such as value (Prentice, McLaughlin, & Brady, 2018;Sung, Kim, & Youn, 2014), motivation , attachment (Lee, Jung, & Seong, 2018), and trust (Lee & Bea, 2006).…”
Section: Limitationsupporting
confidence: 56%
“…From a similar view, the research of students in a public university in Ghana, Mattah, Kwarteng, and Mensah (2018) found positive relationships among education service quality, satisfaction and loyalty. In the case of a private university in Ireland, Prentice, McLaughlin, and Brady (2018) studied the relationships between service quality, value and satisfaction on student customer intentions and behavior, and found that perceptions of good service quality will have a significant positive impact on satisfaction. In a study of Saudi Arabian private higher education institutions, Azam (2018) hypothesized about the relationship between service quality dimensions and satisfaction and highlighted that there is a significant relationship among the four dimensions (Assurance, Empathy, Reliability, Responsiveness) and customer satisfaction and behavioral intentions.…”
Section: The Impact Of Service Quality On Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Good service quality will be an advantage for educational institutions. Feigenbaum [3], states that quality is full customer satisfaction. A quality product if it can provide full satisfaction to consumers, namely in accordance with what consumers expect for a product / service.…”
Section: Introductionmentioning
confidence: 99%
“…In the forefront of my mind when making the contributor call for this special issue is the fact that, as a psychologist myself who works in a business third-level college, who has taught business students in relation to research methods and management techniques, published articles in the marketing field (e.g. Prentice, Brady and McLaughlin, 2018) and co-authored a book on virtual leadership (Brady and Prentice, 2019), I have my own perspective on the partnership between psychology and business and the possibilities that can develop from that combination. However, to remain neutral, the call was as broad as possible with many possible psychology and business related areas suggested from which academic papers, original research, reflections, review papers, case studies, book reviews, original creative work, and interviews with key thinkers and practitioner updates could come.…”
mentioning
confidence: 99%